Enhancing private and public risk sharing: Lessons from the literature and reflections on the COVID-19 crisis - Jacopo Cimadomo; Esther Gordo; Alessandra Anna Palazzo (European Central Bank (ECB), 2022)
This article surveys the literature on consumption risk sharing, focusing on the findings for the euro area and for the United States, but also presenting evidence for other countries. The literature examined found that risk sharing is higher in more mature federations, such as the United States, than in the euro area. The papers surveyed suggest that state/country-specific output shocks are primarily smoothed out through the capital and credit channel, whereas the fiscal channel as a minor role, especially in the euro area. Overall, about 70% of shocks is smoothed in the United States while just 40% in the euro area. At the same time, our analysis of the response to the COVID-19 crisis indicates that risk sharing in the euro area has been more resilient than it was during the global financial crisis of 2008-09. Overall, our results point to the need for further improvements to the private and public risksharing channels in the euro area to ensure more effective cushioning against asymmetric shocks and to boost progress towards the completion of European Monetary Union (EMU).
Keywords: C23; E62; G11; G15; 330; Risk sharing; COVID-19 crisis; EMU reform